Characterization of cure of carbon/epoxy prepreg used in aerospace field - Costa,Michelle Leali (2005)
Carbon/epoxy 8552 prepreg is a thermoplastic toughened high-performance epoxy being used in the manufacture of advanced army material. Understanding the cure behavior of a thermosetting system is essential in the development and optimization of composite fabrication processes. The cure kinetics and rheological behavior were evaluated using a differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and a rheometer. Values of the kinetic parameters were obtained from dynamic DSC scans using an nth order reaction model. Rheological measurements as a function of temperature and time were made for the prepreg system. The manufacturer's recommended cure cycle was evaluated and considered adequate to consolidated the studied system.